Glyphosate exposure in early pregnancy and reduced fetal growth: a prospective observational study of high-risk pregnancies - Roy R. Gerona; Jill L. Reiter; Igor Zakharevich; Cathy Proctor; Jun Ying; Robin Mesnage; Michael Antoniou; Paul D. Winchester (BMC, 2022)
Abstract Background Prenatal glyphosate (GLY) exposure is associated with adverse reproductive outcomes in animal studies. Little is known about the effects of GLY exposure during pregnancy in the human population. This study aims to establish baseline urine GLY levels in a high-risk and racially diverse pregnancy cohort and to assess the relationship between prenatal GLY exposure and fetal development and birth outcomes. Methods Random first trimester urine specimens were collected from high risk pregnant women between 2013 and 2016 as part of the Indiana Pregnancy Environmental Exposures Study (PEES). Demographic and clinical data were abstracted from mother and infant medical records. Urine glyphosate levels were measured as a proxy for GLY exposure and quantified using liquid chromatography-tandem mass spectrometry. Primary outcome variables included gestation-adjusted birth weight percentile (BWT%ile) and neonatal intensive care unit (NICU) admission. Relationships between primary outcome variables and GLY exposure were assessed using univariate and multivariate linear and logistic regression models. Results Urine GLY levels above the limit of detection (0.1 ng/mL) were found in 186 of 187 (99%) pregnant women. Further analyses were limited to 155 pregnant women with singleton live births. The mean age of participants was 29 years, and the majority were non-Hispanic white (70%) or non-Hispanic Black (21%). The mean (± SD) urine GLY level was 3.33 ± 1.67 ng/mL. Newborn BWT%iles were negatively related to GLY (adjusted slope ± SE = -0.032 + 0.014, p = 0.023). Infants born to women living outside of Indiana's large central metropolitan area were more likely to have a lower BWT%ile associated with mother's first trimester GLY levels (slope ± SE = -0.064 ± 0.024, p = 0.007). The adjusted odds ratio for NICU admission and maternal GLY levels was 1.16 (95% CI: 0.90, 1.67, p = 0.233). Conclusion GLY was found in 99% of pregnant women in this Midwestern cohort. Higher maternal GLY levels in the first trimester were associated with lower BWT%iles and higher NICU admission risk. The results warrant further investigation on the effects of GLY exposure in human pregnancies in larger population studies.